Construction of Reading Meaning for Application User Wattpad Indonesia - Genny Gustina Sari; Welly Wirman; Vindriana Adios (Ikatan Sarjana Komunikasi Indonesia, 2020)
Wattpad is an application for reading mobile comes to help people to read and share their story by reading. This study aims to determine how the user of Wattpad makes sense about reading activity and how the meaning of Wattpad for them to use Wattpad as media. This research uses qualitative descriptive methods with a phenomenology-virtual approach. The subject of the research consisted of three Wattpad ambassadors in Indonesia selected by the purposive technique. The results of this research are the meaning of reading by the user is (1) Habit, this explains about reading as an activity they have started since the child until now and that becomes activity as habitually for the informants. (2) Necessary, that means the informants need to read every time (3) Addictive, that's the information means addict to read and find some books that they like. Meanwhile, the meaning of Wattpad as media, find two means there are (1) Second After Books, that's mean Wattpad only alternative media for reading. (2) Jumping Stone, it means Wattpad as the platform to meet the user masterpiece to the readers and make them be a real writer.